The effect of different alcohol fuels on the performance, emission and combustion characteristics of a gasoline engine - SAYIN, CENK (ELSEVIER SCI LTD, 2014)
In this experimental study, the effect of alcohol (ethanol and methanol) use on the performance, emissions and combustion characteristics of a low power single-cylinder engine described the rated power output of the engine e. g. 2 kW were investigated and the results were compared with conventional gasoline operation. The tests were performed at full-throttle valve opening and variable engine speeds. The results show that the use of alcohol fuels increased the engine torque, brake specific fuel consumption (BSFC), thermal efficiency and combustion efficiency. In addition, the cylinder gas pressure and heat release rate occurred earlier; carbon dioxide (CO2) emission increased while hydrocarbon (HC), carbon monoxide (CO) and nitrogen oxides (NOx) emissions decreased. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Alcohol fuels; Combustion; Emissions; Engine performance; Low power engine; ETHANOL-GASOLINE; EXHAUST EMISSIONS; COMPRESSION RATIO; BLENDS